2021
DOI: 10.1101/2021.07.30.454458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactive effects of microplastic pollution and heat stress on reef-building corals

Abstract: Plastic pollution is an emerging stressor that increases pressure on ecosystems such as coral reefs that are already challenged by climate change. However, the effect of plastic pollution in combination with global warming is largely unknown. Thus, the goal of this study was to determine the cumulative effect of microplastic pollution with that of global warming on reef-building coral species and to compare the severity of both stressors. For this, we conducted a series of three controlled laboratory experimen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
4
5
0
Order By: Relevance
“…In fact, overall gene expression profiles were indistinguishable between the ambient and microplastics treatments, and an effect of microplastics was only apparent when looking at the expression of top 1,000 genes. This result corroborates previous work reporting negligible effects of microplastics on coral physiology, bleaching susceptibility, and mortality (Reichert et al, 2021; Plafcan and Stallings, 2022) and supports the hypothesis that corals that rely more heavily on heterotrophy may be more impacted by this stressor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, overall gene expression profiles were indistinguishable between the ambient and microplastics treatments, and an effect of microplastics was only apparent when looking at the expression of top 1,000 genes. This result corroborates previous work reporting negligible effects of microplastics on coral physiology, bleaching susceptibility, and mortality (Reichert et al, 2021; Plafcan and Stallings, 2022) and supports the hypothesis that corals that rely more heavily on heterotrophy may be more impacted by this stressor.…”
Section: Discussionsupporting
confidence: 91%
“…Of the work to date examining global change stressors and microplastics, results are variable and species dependent (Axworthy and Padilla-Gamiño, 2019; Huang et al, 2021). For example, recent work found that warming led to consistent reductions in fitness-related traits in corals, while microplastics resulted in mixed responses (Reichert et al, 2021). Similarly, another study found that microplastics had no effect on Symbiodiniaceae cell density under ambient or elevated temperatures (Plafcan and Stallings, 2022), suggesting that microplastics may represent a minor stressor when compared to warming.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, overall gene expression profiles were indistinguishable between the ambient and microplastics treatments, and an effect of microplastics was only apparent when looking at the expression of top 1,000 genes. This result corroborates previous work reporting negligible effects of microplastics on coral physiology, bleaching susceptibility, and mortality (Reichert et al, 2021;Plafcan and Stallings, 2022) and supports the hypothesis that corals that rely more heavily on heterotrophy may be more impacted by microplastic pollution.…”
Section: Microplastics Alone Do Not Drive Strong Gene Expression Resp...supporting
confidence: 91%
“…Of the work to date examining global change stressors and microplastics, results are variable and species dependent (Axworthy and Padilla-Gamiño, 2019;Huang et al, 2021). For example, recent work found that warming led to consistent reductions in fitness-related traits in corals, while microplastics resulted in mixed responses (Reichert et al, 2021). Similarly, another study found that microplastics had no effect on Symbiodiniaceae cell density under ambient or elevated temperatures (Plafcan and Stallings, 2022), suggesting that microplastics may represent a minor stressor when compared to warming.…”
Section: Introductionmentioning
confidence: 99%
“…Corals are under threat due to ocean warming, pollution, and acidification (Hoegh-Guldberg et al, 2007;Reichert et al, 2021). The recent Intergovernmental Panel on Climate Change (IPCC) report suggests an increase of at least 1.5°C which will further affect corals.…”
Section: Introductionmentioning
confidence: 99%